1999
DOI: 10.1029/1998jb900095
|View full text |Cite
|
Sign up to set email alerts
|

P and S velocity structure of the Yellowstone volcanic field from local earthquake and controlled‐source tomography

Abstract: Abstract. The three-dimensional P and S velocity (from VF/V s ratios) distribution and improved hypocenters for the Yellowstone volcanic field have been determined from inversion of first arrival times from 7942 local earthquakes and 16 controlled-source explosions. The P velocity model has an rms residual of ñ 0.09 s, whereas the Vp/Vs ratio model (calculated from 511 earthquakes) has an rms residual of ñ 0.29 s. High P and S velocities outside the Yellowstone caldera represent thermally undisturbed basement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 17 publications
(11 reference statements)
3
90
1
Order By: Relevance
“…Benz and Smith (1984) showed two zones of unusually low velocities in the northeast and the southwest part of the caldera. Miller and Smith (1999) found a caldera-wide 15 percent decrease in P-wave velocities compared to the surrounding area at depths of 6 to 12 km. In addition, they found a smaller but more pronounced low-velocity zone that underlies the northeast caldera rim from depths less than 2 km and explained this by the presence of a saturated fluid (gas or gas/liquid) filling fractures, and possibly the presence of hydrothermally altered volume of rock (Miller and Smith, 1999).…”
Section: Present-day Magmatic System and Crustal Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Benz and Smith (1984) showed two zones of unusually low velocities in the northeast and the southwest part of the caldera. Miller and Smith (1999) found a caldera-wide 15 percent decrease in P-wave velocities compared to the surrounding area at depths of 6 to 12 km. In addition, they found a smaller but more pronounced low-velocity zone that underlies the northeast caldera rim from depths less than 2 km and explained this by the presence of a saturated fluid (gas or gas/liquid) filling fractures, and possibly the presence of hydrothermally altered volume of rock (Miller and Smith, 1999).…”
Section: Present-day Magmatic System and Crustal Structurementioning
confidence: 99%
“…Miller and Smith (1999) found a caldera-wide 15 percent decrease in P-wave velocities compared to the surrounding area at depths of 6 to 12 km. In addition, they found a smaller but more pronounced low-velocity zone that underlies the northeast caldera rim from depths less than 2 km and explained this by the presence of a saturated fluid (gas or gas/liquid) filling fractures, and possibly the presence of hydrothermally altered volume of rock (Miller and Smith, 1999). A local earthquake tomographic study by Husen, Smith, and Waite (2004) confirmed the existence of a low P-wave velocity body beneath the Yellowstone Caldera at depths greater than 8 km, possibly representing hot, crystallizing magma.…”
Section: Present-day Magmatic System and Crustal Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Geophysical and geochemical evidence suggests that subvolcanic reservoirs are, in many cases, composed of multiple pockets of eruptible magma that may have been separated for most of their lifetime (Miller & Smith 1999;Bachmann & Bergantz 2008;Cashman & Giordano 2014;Cooper & Kent 2014;Ellis et al 2014;Wotzlaw et al 2014). The accumulation of residual melt in these separate reservoirs has been modelled hitherto solely as a single, large accumulation in the upper portion of a single reservoir.…”
Section: Architecture Of Subvolcanic Reservoirsmentioning
confidence: 99%
“…In turn, such small perturbations can be detected as changes of seismic wave properties based on seismic noise (e.g. Ratdomopurbo & Poupinet 1995;Miller & Smith 1999;Grêt et al 2005;Wegler et al 2006). However, despite considerable efforts in the past, the precise monitoring of the location of subsurface changes has proven to be difficult, meaning that there is a need for novel observational methods to obtain information about the ongoing subsurface changes and their relation to volcanic processes.…”
Section: Rayleigh and Love Waves 3-d Imagingmentioning
confidence: 99%